Analisis Performa Sepeda Motor Sistem Injeksi 110 CC Menggunakan ECU Standar dan ECU Standar Remap - Pratama, Fharhan Hidayat; Abidin, Asroful; Bahri, Mokh. Hairul (Journal of Engineering Science and Technology, 2024)
The aim of this research is to analyze the effect of remapping maximum engine speed with standard ECU variations and ECU remapping on the performance of a 110cc injection motorbike engine. In this research, dynotest testing was carried out on 110cc injection motorbikes of various types of standard Electronic Control Unit (ECU) and standard Electronic Control Unit (ECU) by taking test results at engine speeds of 3000 rpm-8000 rpm with a range of 1000 rpm. The calculation method is to calculate power and torque. The test results using a dynotest tool based on power and torque obtained data as above, where the highest power and torque from the standard ECU variable was obtained at 7.4 HP and the highest torque at 9.38 Nm. Meanwhile, using the standard ECU remap, the highest power is 7.6 hp and the highest torque is 9.52. The results of the dynotest test and also calculations from Origin Pro with a comparison using a standard ECU and a remap standard ECU concluded that the use of a remap standard ECU can provide an increase in power and torque in the motorbike engine. When using a standard ECU remap, the results show that the standard ECU that has been remapped actually provides higher improvement results than the standard ECU that has not been remapped.